Assessing equilibrium exchange rates in CEE acceding countries: can we have DEER with BEER without FEER? A critical survey of the literature - Balázs Égert (Bank of Finland, Institute for Economies in Transition (BOFIT), 2004)
The ambition of this paper is to provide a thorough overview of equilibrium exchange rates in the acceding countries of Central and Eastern Europe.Therefore, theoretical models of equilibrium exchange rates are reviewed first and presented in a structured way.Subsequently, the existing body of the empirical literature aimed at investigating real exchange rate determination and possible misalignments is analyzed in a systematic manner.Finally, an attempt is made to sum up where we stand at the moment and what the major shortcomings of the approaches currently used in the literature are.
URN:NBN:fi:bof-201408071901
Keywords: 330